2020
DOI: 10.3390/plants9010114
|View full text |Cite
|
Sign up to set email alerts
|

HD-ZIP I Transcription Factor (PtHB13) Negatively Regulates Citrus Flowering through Binding to FLOWERING LOCUS C Promoter

Abstract: For floral induction in adult citrus, low temperature is one of the most important environmental factors. FLOWERING LOCUS C (FLC) plays a very important role in low-temperature-induced Arabidopsis flowering by repressed FLC expression under exposure to prolonged low-temperature conditions. However, little is known about the FLC regulation mechanism in perennial woody plants such as citrus. In this study, the functions of citrus FLC homolog (PtFLC) were investigated by ectopic expression in Arabidopsis. Transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…This regulation could be the outcome of the direct interaction of START domain-containing proteins with lipid/sterol proteins or by third mediator protein [25]. A study supported this notion by reporting that an HD-ZIP class IV gene regulates the phospholipid signaling in arabidopsis roots [26]. Another report concluded that the START domain is essential for the proper functioning of HD-ZIP genes in the cotton plant [27].…”
Section: Structural Characteristics Of Hd-zip Gene Familymentioning
confidence: 98%
See 2 more Smart Citations
“…This regulation could be the outcome of the direct interaction of START domain-containing proteins with lipid/sterol proteins or by third mediator protein [25]. A study supported this notion by reporting that an HD-ZIP class IV gene regulates the phospholipid signaling in arabidopsis roots [26]. Another report concluded that the START domain is essential for the proper functioning of HD-ZIP genes in the cotton plant [27].…”
Section: Structural Characteristics Of Hd-zip Gene Familymentioning
confidence: 98%
“…For example, the HDZI-4 promoter drives DREB/CBF expression under severe drought conditions, which mitigates the negative effects of drought stress and restricts the declination in yield and other growth attributes in wheat and barley [25]. Recently, Ma et al [26] addressed the crucial role of ATHB13 in floral induction. Flower induction at an appropriate time is crucial for seed setting, survival, and germination [27,28].…”
Section: Role Of Hd-zip Genes Family In Plant Growth and Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In citrus, seasonal fluctuation in expression of FLC homologs was reported (Zhang et al ., 2009; Y.‐J. Ma et al ., 2020), suggestive of negative regulation of citrus flowering. Furthermore, a mandarin FLC CcMADS19 (Hou et al ., 2014; Agustí et al ., 2020) acted to repress the citrus FT and drive the biennial bearing pattern.…”
Section: Introductionmentioning
confidence: 99%
“…For example, FLOWERING LOCUS C ( FLC ) encodes a specific MADS-box protein and as a typical flowering suppressor [ 10 , 11 , 12 ]. Citrus FLC homolog is conserved with model plants, but it regulates the phase changes of citrus through alternative splicing [ 13 , 14 ]. AGAMOUSLIKE16 ( AGL16 ) is a target of miR824, which inhibits plant flowering [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%